KEMAMPUAN TIGA ISOLAT KELOMPOK AKTINOMISET BERBEDA DALAM PRODUKSI ENZIM MANNANASE - Fahrurrozi Fahrurrozi (Widyariset, 2022)
Three different species of Actinomycetes namely Streptomyces alboniger, Saccharopolyspora flava, and Streptacidiphilus lutealbus were investigated for the ability of producing mannanase enzyme. All isolates were able to hydrolyze mannan substrate differently. The mannanase activity from S. flava, S. alboniger, and S. luteualbus were 4.764; 0.110; 0.614 U/ml respectively. S. flava was also being predicted to produce sellulase and xylanase by its ability to grow in a wide range of media containing mannan, xylan, CMC, palm kernel, coconut kernel, and porang. The mannanase produced by S. flava was also maintained its activity at high temperature (50-60oC) therefore being considered as thermostable enzyme. TLC analysis revealed the occurrence of oligosaccharide as a product from substrate-enzyme reaction